Bowhead and Gray Whale Distributions, Sighting Rates, and Habitat Associations in the Eastern Chukchi Sea, Summer and Fall 2009–15, with a Retrospective Comparison to 1982–91 - Clarke, Janet T.; Kennedy, Amy S.; Ferguson, Megan C. (ARCTIC, 2016)
We analyzed data from line-transect aerial surveys for marine mammals conducted in the eastern Chukchi Sea (67˚–72˚ N, 157˚–169˚ W) in July to October of 2009–15 to investigate bowhead and gray whale distributions, behaviors, sighting rates, and habitat selection preferences, the last of which allowed direct comparison with results from data collected in this area in 1982–91. Bowhead whales use the eastern Chukchi Sea primarily for migrating between the Beaufort Sea and the Bering Sea, while gray whales use the area to feed on locally abundant benthic amphipods and other prey. Bowhead whales were observed during all survey months and were distributed up to 300 km offshore west and southwest of Point Barrow, Alaska, but without a defined migratory corridor in either summer (July-August) or fall (September-October). Bowhead whale sighting rates (whales per km on effort) were highest in the shelf/trough (51–200 m North) depth zone in the northeastern Chukchi Sea in both summer and fall. This pattern was reflected in habitat selection ratios, which found bowhead whales in summer and fall selecting primarily shelf/trough habitat in the northeastern Chukchi Sea, with shelf habitat (36 – 50 m) being preferred secondarily. Gray whales were observed in all survey months and were distributed primarily within ~95 km of shore between Point Barrow and Icy Cape in the northeastern Chukchi Sea, and about 60–115 km southwest of Point Hope in the southern Chukchi Sea. In both summer and fall, gray whale sighting rates and habitat selection ratios were highest in the shelf/trough (51–200 m South) depth zone in the southern Chukchi Sea. In the northeastern part of the study area, gray whale sighting rates and habitat selection ratios both identified coastal habitat (≤ 35 m) as preferred habitat in summer and shelf/trough (51–200 m North) as preferred habitat in fall. Distribution and habitat associations of bowhead and gray whales remained similar over the 34-year time span with one exception: gray whale preference for ...